Proceedings of the Ninth International Conference on Architectural Support for Programming Languages and Operating Systems 2000
DOI: 10.1145/378993.379006
|View full text |Cite
|
Sign up to set email alerts
|

System architecture directions for networked sensors

Abstract: Technological progress in integrated, low-power, CMOS communication devices and sensors makes a rich design space of networked sensors viable. They can be deeply embedded in the physical world or spread throughout our environment. The missing elements are an overall system architecture and a methodology for systematic advance. To this end, we identify key requirements, develop a small device that is representative of the class, design a tiny event-driven operating system, and show that it provides support for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1,194
0
19

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,927 publications
(1,215 citation statements)
references
References 9 publications
2
1,194
0
19
Order By: Relevance
“…The transmission range of the nodes is 50m and is the same for each node. The energy consumption for transmission / reception of a single byte is 16.25/12.5 μJ, and we assume that the length of each event message is 36 bytes [22][23][24]. The energy consumption for one verification operation of a MAC is 75 μJ.…”
Section: Methodsmentioning
confidence: 99%
“…The transmission range of the nodes is 50m and is the same for each node. The energy consumption for transmission / reception of a single byte is 16.25/12.5 μJ, and we assume that the length of each event message is 36 bytes [22][23][24]. The energy consumption for one verification operation of a MAC is 75 μJ.…”
Section: Methodsmentioning
confidence: 99%
“…We have created a platform for networked sensor systems: (1) software components specified in nesC [3], a native programming language for sensor software; (2) hardware components specified in Verilog; (3) bridge compo- nents specified in a BSL that is similar to the language used in Figure 4 while interactions with software components are conducted through function calls instead of messagepassing. The platform-specific libraries are populated as we used ESIDE to re-engineer the networked sensor systems included in the TinyOS [5] distribution. The libraries are further expanded as we re-engineered the sensor systems in the CodeBlue [14] distribution.…”
Section: Component-based Co-designmentioning
confidence: 99%
“…We have instantiated EADL for two networked sensor platforms with different software languages: xUML [10] (a designlevel language) and nesC [3] (an implementation-level language). Furthermore, we have applied EADL in capturing architectures of networked sensor systems [5,14] and guiding their HW/SW co-verification. EADL has demonstrated its flexibility in platform-oriented instantiation and its effectiveness in capturing architectures and patterns and in simplifying formulation of system and component properties.…”
Section: Introductionmentioning
confidence: 99%
“…The preliminary research investigates the differences of the multi-threaded MAN-TIS [2] and the event-based TinyOS [1] operating systems. More details on the preliminary research can be found in [7].…”
Section: Preliminary Researchmentioning
confidence: 99%
“…Hence, the event-based TinyOS [1] is currently the preferred operating system for sensor networks. Event-based operating systems are not very useful in situations where tasks have strict processing deadlines.…”
Section: Introductionmentioning
confidence: 99%